2020
DOI: 10.21203/rs.2.24460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preoperative adjuvant therapy for locally advanced and recurrent/metastatic gastrointestinal stromal tumors: a retrospective study

Abstract: Background Preoperative imatinib mesylate therapy for gastrointestinal stromal tumors (GISTs) is controversial. This study aimed to explore the clinical efficacy and optimal duration of preoperative imatinib mesylate (IM) therapy in patients with locally advanced and recurrent/metastatic GISTs. Methods We retrospectively examined patients who received preoperative imatinib mesylate therapy from January 2013 to December 2018 at Xiangya Hospital, Central South University and the Second Xiangya Hospital of Centra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…7 12 42 Furthermore, it is now known that location has an impact in tumor response to TKIs, since non-gastric GISTs have worse response to these drugs than their gastric counterparts. 15…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 12 42 Furthermore, it is now known that location has an impact in tumor response to TKIs, since non-gastric GISTs have worse response to these drugs than their gastric counterparts. 15…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 20% of the patients with GIST present with metastases at the time of diagnosis. 15 The tumor usually metastasizes to the liver and peritoneum. 1 Metastases to lymph nodes are rare, except in pediatric and syndromic GISTs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…GIST could occur throughout the gastrointestinal tract, most frequently in the stomach and small intestine, and relatively rare in rectum [9,10]. Our research found that most of rectal GIST occurred in the lower location of the rectum, with 26 (81.2%) of the 32 patients located occurred within 5 cm to the anal edge, besides, Shu P, et al also found that 61(85.9%) of 71 rectal GIST located within 5 cm to the anal edge [11].…”
Section: Discussionmentioning
confidence: 99%